Dampak Intervensi Edukasi dan Aplikasi Pengingat Minum Obat terhadap Pengetahuan dan Kepatuhan Pasien Tuberkulosis Paru di Puskesmas di Kota Bandung - Reyaan, Irianti Bahana Maulida; Faustincia, Ivena; Zazuli, Zulfan (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Tuberculosis (TB) patient compliance with ongoing therapy and knowledge regarding TB has an impact on the cure rate. Despite implementing various strategies, the prevalence of TB in Indonesia remains high, and the success rate of its treatment is still below the global average, potentially leading to continued transmission of TB within the community. This study aims to determine the improvement of knowledge and compliance among pulmonary TB patients following an intervention involving education and the use of a medication reminder application in two community health centers in the city of Bandung. The research design was experimental, where 29 subjects recruited were randomized into two groups: one group receiving additional education and introduction to the mobile application (Jadwal Minum Obat), and the other group receiving only counseling at the health centers. Primary data that was collected include baseline test scores and final test scores of subjects based on the KATUB-Q questionnaire. Patient compliance was assessed using the self-assessment method with the MARS-5 questionnaire and the pill count method. The subjects' experiences in the intervention group while using the mobile application were also documented. A total of 16 subjects completed the study. The education method and medication reminder application used in this study have not significantly improved the knowledge and compliance of pulmonary TB patients in taking their medication (p > 0.05). However, percentage of consumed medication compared to the prescribed medication in the intervention group higher than the control group (87.4 ± 4.8% vs 78.8 ± 8.3%). Subjects found the application useful, though there were still some shortcomings. Further research with a larger sample size using an improved medication reminder application is needed.